2011
DOI: 10.1007/s10585-011-9427-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte induced re-expression of E-cadherin in breast and prostate cancer cells increases chemoresistance

Abstract: Post-extravasation survival is a key rate-limiting step of metastasis; however, not much is known about the factors that enable survival of the metastatic cancer cell at the secondary site. Furthermore, metastatic nodules are often refractory to current therapies, necessitating the elucidation of molecular changes that affect the chemosensitivity of metastases. Drug resistance exhibited by tumor spheroids has been shown to be mediated by cell adhesion and can be abrogated by addition of E-cadherin blocking ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 37 publications
5
94
0
3
Order By: Relevance
“…We have reported that hepatocyte co-culture can lead to up-regulation or re-expression of E-cadherin even in highly aggressive carcinoma cells (12,13). Herein, we show that this phenotypic switch extends to other epithelial markers of cell-cell cohesion including ZO-1 and connexin 43 (Fig.…”
Section: Hepatocyte-educated Prostate Cancer Cells Re-express E-cadhesupporting
confidence: 51%
See 2 more Smart Citations
“…We have reported that hepatocyte co-culture can lead to up-regulation or re-expression of E-cadherin even in highly aggressive carcinoma cells (12,13). Herein, we show that this phenotypic switch extends to other epithelial markers of cell-cell cohesion including ZO-1 and connexin 43 (Fig.…”
Section: Hepatocyte-educated Prostate Cancer Cells Re-express E-cadhesupporting
confidence: 51%
“…We have previously shown that E-cadherin expression in prostate cancer metastases is inversely correlated with the size of metastasis (13), suggesting a metastable nature to the reversion toward an epithelial phenotype. To explore the relationship between the colony size and E-cadherin expression patterns in vitro, the cell number per colony with different E-cadherin expression levels was determined.…”
Section: Hepatocyte-educated Prostate Cancer Cells Re-express E-cadhementioning
confidence: 94%
See 1 more Smart Citation
“…Par exemple, l'adhérence de cellules tumorales myélomateuses aux cellules stromales de la moelle osseuse par l'intermédiaire de l'intégrine 1 stimule leur production d'interleukine-6 (IL-6) qui, à son tour, protège les cellules cancéreuses [9]. Ces cellules cancéreuses, mises en contact avec des hépatocytes, expriment de nouveau la E-cadhérine, favorisant leur chimiorésistance [10]. Le contact entre les cellules leucémiques et la niche de la moelle osseuse favorise leur résistance aux inhibiteurs de kinases, comme le sorafenib et le SU5614 [11].…”
Section: Mec Cellule Tumoraleunclassified
“…In addition to microenvironmental drivers of EMT, there is also evidence that MET in metastatic colonization may be mediated by the microenvironment. For example, DU-145 cells re-express Ecadherin upon coculture with human hepatocytes, and reexpression of E-cadherin also leads to chemoresistance, suggesting that MET may serve a protective role against chemotherapeutics at metastatic sites [152]. Similarly, coculture of DU-145 and PC-3 cells with primary rat hepatocytes leads to re-expression of E-cadherin and cytokeratin and reduced levels of vimentin [153], and coculture of ARCaP M cells with bone marrow stromal cells results in re-expression of Ecadherin in the ARCaP M cells [154], lending further support for the idea that microenvironmental cues at the sites of metastatic dissemination may lead to MET.…”
Section: Microenvironmental Cues As Mediators Of Epmentioning
confidence: 99%